They Don't See a Lot of People My Color: A Mixed Methods Study of Racial/Ethnic Stereotype Threat Among Medical Students on Core Clerkships. (November 2020) - Bullock, Justin L.; Lockspeiser, Tai; del Pino-Jones, Amira; Richards, Regina; Teherani, Arianne; Hauer, Karen E.
Abstract : Purpose: Stereotype threat is an important psychological phenomenon in which fear of fulfilling negative stereotypes about one's group impairs performance. The effects of stereotype threat in medical education are poorly characterized. This study examined the prevalence of racial/ethnic stereotype threat amongst fourth-year medical students and explored its impact on students' clinical experience. Method: This was an explanatory sequential mixed methods study at 2 institutions in 2019. First, the authors administered the quantitative Stereotype Vulnerability Scale (SVS) to fourth-year medical students. The authors then conducted semistructured interviews among a purposive sample of students with high SVS scores, using a qualitative phenomenographic approach to analyze experiences of stereotype threat. The research team considered reflexivity through group discussion and journaling. Results: Overall, 52% (184/353) of students responded to the survey. Collectively, 28% of students had high vulnerability to stereotype threat: 82% of Black, 45% of Asian, 43% of Latinx, and 4% of White students. Eighteen students participated in interviews. Stereotype threat was a dynamic, 3-stage process triggered when students experienced the workplace through the colored lens of race/ethnicity by standing out, reliving past experiences, and witnessing microaggressions. Next, students engaged in internal dialogue to navigate racially charged events and workplace power dynamics. These efforts depleted cognitive resources and interfered with learning. Finally, students responded and coped to withstand threats. Immediate and deferred interventions from allies reduced stereotype threat. Conclusions: Stereotype threat is common, particularly among non-White students, and interferes with learning. Increased minority representation and developing evidence-based strategies for allyship around microaggressions could mitigate effects of stereotype threat. Abstract : Supplemental Digital Content is available in the text.